Perspective of Need for First Aid Education in Bulgarian Schools - Daniela Baleva (International Journal of First Aid Education)
Background: First aid and disaster response training for school teachers is not mandatory in many countries, including the Republic of Bulgaria, despite its importance for protecting lives and reducing long-term negative effects of injuries to students on school premises. Methods: A sample of 419 teachers from 26 public and private schools in different cities, towns, and villages in all the six NUTS 2 level regions in Bulgaria filled in questionnaires in order to examine their current level of first aid and disaster response training and motivation for improving it. Chi-square, Cramér‘s V, and p-values were calculated in order to explore possible factors influencing teachers’ motivations for learning first aid. Results: Approximately 59% of respondents state their willingness to undergo further first aid and disaster response training. Analyzed data showed negligible relationships between teachers’ desire to improve the level of their first aid and disaster response training and the type of school they teach in. A stronger relationship between the desire of teachers to improve their first aid training and having witnessed a situation requiring first aid exists but the effect size is weak. The analysis shows the discrepancies between the confidence and decisiveness of teachers reported during the survey and the level of their first aid training. Conclusion: The majority of teachers that participated in the research wished to improve their first aid skills. This requires further research on the appropriate forms, duration, and means for organizing such training so that in the short term the general level of first aid training of teachers in the country would increase. The results of the conducted survey do not clearly show the factors influencing the lack of motivation of the rest of the teachers. Further research in this aspect could present possibilities for improving the level of first-aid training of teachers.